2007
DOI: 10.1007/s00424-007-0236-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate supplementation during prolonged cycling exercise spares muscle glycogen but does not affect intramyocellular lipid use

Abstract: Using contemporary stable-isotope methodology and fluorescence microscopy, we assessed the impact of carbohydrate supplementation on whole-body and fibertype-specific intramyocellular triacylglycerol (IMTG) and glycogen use during prolonged endurance exercise. Ten endurance-trained male subjects were studied twice during 3 h of cycling at 63±4% of maximal O 2 uptake with either glucose ingestion (CHO trial; 0.7 g CHO kg −1 h −1 ) or without (CON placebo trial; water only). Continuous infusions with [U-13 C] pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 51 publications
2
43
0
1
Order By: Relevance
“…These findings are in line with previous reports where, during exercise, fat oxidation is favored following an LCHO meal, whereas CHO oxidation is favored in the case of an HCHO meal (27,40). The results also corroborate with the findings of Stellingwerff et al (36) who showed that low-CHO high-fat explicitly impairs rather than spares glycogen utilization during exercise by reducing glycogenolysis. In this study, when the participants arrived at the laboratory in a fasted state and therefore had low endogenous CHO availability, the low-CHO exogenous supply from the LCHO meal undoubtedly impaired exercise performance and hastened fatigue, as evident during the sMVC task (2).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with previous reports where, during exercise, fat oxidation is favored following an LCHO meal, whereas CHO oxidation is favored in the case of an HCHO meal (27,40). The results also corroborate with the findings of Stellingwerff et al (36) who showed that low-CHO high-fat explicitly impairs rather than spares glycogen utilization during exercise by reducing glycogenolysis. In this study, when the participants arrived at the laboratory in a fasted state and therefore had low endogenous CHO availability, the low-CHO exogenous supply from the LCHO meal undoubtedly impaired exercise performance and hastened fatigue, as evident during the sMVC task (2).…”
Section: Discussionsupporting
confidence: 93%
“…Consuming pre-exercise CHO may help increase its availability by maximizing the fuel stored before exercise, whereby up to 42% muscle glycogen is replenished following a pre-exercise meal (9). Consequently, the delay in fatigue manifestation could be augmented by muscle glycogen sparing (36), liver glycogen sparing (16), and maintenance of plasma glucose and the CHO oxidation rate (8). However, other studies suggest that low glycogen may not be the cause of reduced exercise performance (24), as high intensity exercise of short duration in nature might not induce significant glycogenolytic effect, hence less dependency on CHO as fuel (18).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of the two test beverages resulted in lower CHO ENDO , potentially decreasing reliance on hepatic glucose utilisation, and permitting glycogen sparing, particularly in type I muscle fibres, during continuous aerobic exercise. Indeed, as the use of carbohydrate beverages has been shown to spare glycogen early into exercise [39], this may provide a subtle benefit late into exercise if CHO TOT is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that carbohydrate (CHO) supplementation can improve long-duration exercise performance by increasing exogenous CHO oxidation and sparing endogenous glycogen content, thus maintaining high rates of CHO oxidation throughout the later stages of prolonged exercise (Coggan and Coyle 1987;Coyle et al 1986;Foskett et al 2008;Jeukendrup 2004;Jeukendrup et al 1999;Neufer et al 1987;StellingwerV et al 2007;Tsintzas and Williams 1998;van Loon et al 1999;Yaspelkis et al 1993). However, CHO supplementation immediately before or during shortduration exercise (e.g., less than 1 h of duration) has also been shown to improve performance (Anantaraman et al 1995;Ball et al 1995;Below et al 1995;Carter et al 2003;el-Sayed et al 1997;Jeukendrup et al 1997;Jeukendrup 2004;Neufer et al 1987), even though this sort of activity is little or not limited at all by endogenous glycogen availability (Jeukendrup et al 1997;McConell et al 2000).…”
Section: Introductionmentioning
confidence: 99%